2011
DOI: 10.1016/j.diff.2011.05.008
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ: A molecular link between systemic metabolic disease and benign prostate hyperplasia

Abstract: The emergent epidemic of metabolic syndrome and its complex list of sequelae mandate a more thorough understanding of benign prostatic hyperplasia and lower urinary tract symptoms (BPH/LUTS) in the context of systemic metabolic disease. Here we discuss the nature and origins of BPH, examine its role as a component of LUTS and review retrospective clinical studies that have drawn associations between BPH/LUTS and type II diabetes, inflammation and dyslipidemia. PPARγ signaling, which sits at the nexus of system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 201 publications
(286 reference statements)
4
28
1
1
Order By: Relevance
“…Furthermore, animal studies have demonstrated that pioglitazone decreased prostate weight in response to a high-fat diet 12 . These observations suggest that PPARγ signaling is an important factor driving the insulin resistance/diabetes and BPH association 8 .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, animal studies have demonstrated that pioglitazone decreased prostate weight in response to a high-fat diet 12 . These observations suggest that PPARγ signaling is an important factor driving the insulin resistance/diabetes and BPH association 8 .…”
Section: Introductionmentioning
confidence: 91%
“…Along with chronic inflammation, it also appears that diabetes mellitus may be associated with an increased risk for developing BPH 5 . Possible mechanisms for such an association include the hyperinsulinemic state observed in type 2 diabetes mellitus, the mitogenic effect of insulin-like growth factor, 6, 7 and chronic obesity-induced inflammation 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise mechanisms by which obesity influences the risk of BPH/LUTS remain unclear, a theory of causation can be supported by animal studies which provide biological underpinnings for the association between the two disorders [5]. Obesity is characterized by enlarged depots of adipose tissue, which are hormonally active and secrete pro-inflammatory cytokines and chemokines that can influence local adipocyte biology as well as prostate health [6].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of a link between MetS and BPH has been explored for almost 20 years [7,8,9,10,11]. Our previous study suggested that MetS is highly prevalent in the BPH population and that it is associated with an increase in total volume and annual prostate growth rate.…”
Section: Introductionmentioning
confidence: 99%